Traffic jam prediction using hazardous material transportation management simulation. (26th August 2021) - Reis, Luiz Antonio; Pereira, Sergio Luiz; Dias, Eduardo Mario; Scoton, Maria Lídia Rebello Pinho Dias
Hazardous materials endanger human lives and the environment, but they are necessary to modern life. Transporting hazardous materials through high-density cities increases the risks of accidents, leakages, or explosions; therefore, their transportation requires surveillance and complex traffic management. Computational simulation prediction is an effective support in reducing risks and finding the optimal solution. To consider the simulation reliable, a methodology considers planning, modelling, verification and validation and application. The model was built by adding complexity and the simulated results are analysed and compared for real-world traffic performance. The results show the influence of improvements in traffic management on traffic jam reduction. The advanced simulation system makes a huge contribution to reducing traffic jams and their consequences on fuel consumption and greenhouse gas emissions.